India - Raipur Gujra village (Punjab) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Dairy farmer Mohamed Fakir from Punjab, India, was interviewed as part of the 'Farmer Testimonial Video Series’. His major concern is that his cows are not producing as much milk as they used to. According to Mohamed, this is largely due to the changing climate, lack of water and infrastructure. Other concerns he deals with are the reduction in fodder production around his village. Farmers instead grow cash crops, he explains, and thus it is getting increasingly difficult to get enough fodder for the animals. In the picture: Girl from Punjab, India.